Prognosis of Severe Covid-19 patients after treatment with Therapeutic Plasma Exchange (TPE) - Khalid, Maliha; Feroze, Faheem; Qamar, Saad Bin; Abbas, Naseem; Farooq, Saeed; Siddiqui, Aisha (Journal of Rawalpindi Medical College, 2022)
OBJECTIVE: To demonstrate the effective role of plasmapheresis in the treatment of Cytokine Release Syndrome associated with severe Covid 19 pneumonia. INTRODUCTION: Covid-19 disease is a deadly contagious disease with milder symptoms to a more severe form with acute respiratory failure, septic shock leading to even death. Literature study showed that in severe Covid-19 patients, a hyper-inflammatory response to initial infection could accelerate to severe hyper-cytokinaemia that could lead to an underlying endothelial dysfunction and multiple organ dysfunction. Thus, removal of these inflammatory cytokines by Therapeutic Plasma Exchange is considered to be an essential part of the treatment of critically ill patients in order to improve their survival rates. METHODOLOGY: Retrospective observational study which included 150 RT-PCR positive patients admitted in Covid ITC, from the time period of 1st February 2021 to 31st July 2021 –removed for blind review---Data was analyzed using SPSS software version 16. Frequencies were calculated along with mean and standard deviation. Chi square and ANOVA test was applied to the data. P value <0.05 was considered statistically significant. Linear regression study was applied to predict the prognosis. RESULTS: Out of 150 patients, 51 patients (34%) were of severe ARDS category of whom 13 (25.5%) developed Cytokine Release Syndrome. They received plasmapheresis therapy subsequently and 7 out of those 13 (53.8%) patients got improved. P- value was found to be significant ( <0.05). Overall, the mortality rate was low with 120/150 (80%) getting discharged successfully. CONCLUSION: Our findings suggest that Therapeutic plasma exchange is beneficial in Cytokine storm caused by SARS-CoV2 removing the inflammatory cytokines and improving symptoms, thereby, avoiding intubation. KEY WORDS: , Therapeutic plasma exchange, Hypercytokinaemia, Cytokine Release Syndrome